“Tell she who see me cry”:: Loves and pain in Craco - MÉLLO, RICARDO PIMENTEL (Revista Vazantes, 2020)
The article analyzes the film “Tell her that she saw me cry” by the young director Maíra Bühler, winner of the competitive exhibition at the 8th Olhar de Cinema - Curitiba International Festival. It is the result of the filmmaker’s experience in the region of Cracolândia, in São Paulo, during the second semester of 2016, in a “social hotel” of the Open Arms Program (DBA), of the Fernando Haddad management, which proposed to take care of people whom live or wander in that region, and who abused or compulsively used psychoactive substances, from the perspective of Harm Reduction. It is an ethnographic film, in the sense of flowing composing itself in the relational experience of the characters, making Cracolândia a lived territory, less than just smoked, following the lives of people whose greatest claim is to live their loves and their pains, without having their bodies crossed by bullets or our prejudiced judgments.